Repurposing bioactive compounds for treating multidrug-resistant pathogens - Hummell, Nicholas A. (J Med Microbiol, 2020)
INTRODUCTION: Antimicrobial development is being outpaced by the rising rate of antimicrobial resistance in the developing and industrialized world. Drug repurposing, where novel antibacterial functions can be found for known molecular entities, reduces drug development costs, reduces regulatory hurdles, and increases rate of success. AIM: We sought to characterize the antimicrobial properties of five known bioactives (DMAQ-B1, carboplatin, oxaliplatin, CD437 and PSB-069) that were discovered in a high-throughput phenotypic screen for hits that extend Caenorhabditis elegans survival during exposure to Pseudomonas aeruginosa PA14. METHODOLOGY: c.f.u. assays, biofilm staining and fluorescence microscopy were used to assay the compounds' effect on various virulence determinants. Checkerboard assays were used to assess synergy between compounds and conventional antimicrobials. C. elegans-based assays were used to test whether the compounds could also rescue against Enterococcus faecalis and Staphyloccus aureus. Finally, toxicity was assessed in C. elegans and mammalian cells. RESULTS: Four of the compounds rescued C. elegans from a second bacterial pathogen and two of them (DMAQ-B1, a naturally occurring insulin mimetic, and CD437, an agonist of the retinoic acid receptor) rescued against all three. The platinum complexes displayed increased antimicrobial activity against P. aeruginosa . Of the molecules tested, only CD437 showed slight synergy with ampicillin. The two most effective compounds, DMAQ-B1 and CD437, showed toxicity to mammalian cells. CONCLUSION: Although these compounds' potential for repurposing is limited by their toxicity, our results contribute to this growing field and provide a simple road map for using C. elegans for preliminary testing of known bioactive compounds with predicted antimicrobial activity.